Performance of Broiler Chicks Fed Graded Levels of Heat - Treated Bambarra Groundnut [Voandzia subterranean (L) thouars] Offals - Asaniyan, E.K.; Akinduro, V.O. (International Journal of Poultry Science, 2008)
Bambarra groundnut (Voandzia subterranean (L) thouars) offals (BGO) steamed for 30 minutes (heat treated) to remove any trypsin inhibitory activity that could occur. The steamed offals were incorporated into broiler starter diets at five different levels of 0%, 15%, 30%, 45% and 60%. Incorporation was at the expense of corn. One hundred and fifty, one-week old Anak broiler chicks were randomly divided among the five treatments and each treatment group of birds was replicated three times with ten birds per replicate. The replacement of corn completely by bambarra offals (60% offal) significantly (P < 0.05) reduced weight gain and significantly (P < 0.05) increased the grammes of feed required per gramme of weight gain. The cost of feed required for a gramme of weight gain significantly (P < 0.05) decreased as quantity of BGO fed increases, with 45% inclusion level showed slightly optimal cost. Feed intake was not significantly (P > 0.05) increased as the percentage inclusion of BGO fed to the birds increased. In all, broiler starter birds can utilize up to 45% BGO inclusion in replacement of maize without any deleterious effect on their performance.